Multi-scale fracture patterns and their effects on gas enrichment in tight sandstones: a case study of the Upper Paleozoic in the Qingshimao gas field, Ordos Basin, China - Wang, Jie; Wang, Jiping; Zhang, Yuanyuan; Zhang, Daofeng; Sun, Lei; Luo, Jianning; Wang, Wei; Gong, Lei; Liu, Zongbao; Gao, Shuai (Frontiers in Earth Science, 2024)
The well-interconnected network formed by multi-scale fractures is a factor for forming high-quality reservoirs and achieving high production in tight sandstone. Taking the Upper Paleozoic of the Qingshimao gas field in the Ordos Basin, China, as an example, based on data from image logs, cores, and thin sections, fine quantitative characterization of multi-scale natural fractures in tight sandstone reservoirs was carried out, and the improvement effect and contribution rate of different scales of fractures on reservoir properties were clarified. We also established a method for dividing network patterns of multi-scale fractures and discussed the effect of each fracture network pattern on the gas enrichment and production capacity. Results indicate regular changes in the length, density, aperture, porosity, permeability, and connectivity of natural fractures at different scales. From the micro-scale to the macro scale, parameters such as fracture aperture, length, connectivity, and permeability significantly increase, especially with an exponential increase in permeability, large-scale fractures can provide higher permeability. The density and porosity of fractures show a decreasing trend; that is, the density of micro-scale fractures is higher, which can provide more storage space. Based on the spatial combination patterns and connectivity of fractures of different scales, four types of fracture network patterns were established for the tight sandstone gas reservoir in the Qingshimao gas field: multi-scale fracture network with high density and multi-orientations, multi-scale fracture network with moderate-high density and dual orientations, small-scale fracture network with moderate density and dual orientations, small-scale fracture network with low density and single orientation. The first fracture network pattern dramatically improves tight sandstone's physical properties and connectivity. However, large-scale fractures may cause vertical connectivity, thus destroying the integrity of the cap layer and causing gas leakage. The second fracture network pattern has moderate-high fracture density and good connectivity, effectively improving tight reservoirs' physical properties and horizontal continuity, making it a favourable area for natural gas enrichment. The third fracture network pattern has moderate fracture density and connectivity, and commercial flow can be obtained after fracturing stimulation. The fourth fracture network pattern has low fracture density and poor connectivity and is unable to form effective reservoirs.